Fenomena Facebook: Keterlibatan Teknologi Komunikasi dalam Perkembangan Komunikasi Manusia - Agustina Zubair (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2010)
The development of communication always connect with the technology development of human being. Concepts and theories which establish in a period will be change in the time where technology dominated human being. The newest technology of internet web 2.0 become a new way to build community where we ca connect in communication network. Interpersonal communication include in the new process of communication in internet based on web 2.0. This is a new era, the era revolting how people communicate each other in social network website.